Exploring Gender Bias and Algorithm Transparency: Ethical Considerations of AI in HRM - Du, Jiaxing (Journal of Theory and Practice of Management Science, 2024)
Opportunities and challenges are introduced by the integration of Artificial Intelligence (AI) into Human Resource Management (HRM). The paragraph discusses the ethical implications of AI applications in HRM, focusing on gender bias and algorithm transparency. It explores how AI-driven decision-making in HRM perpetuates gender bias, the importance of transparent algorithms for trust and accountability, and the role of regulatory frameworks in safeguarding ethical standards. The paper aims to provide a comprehensive analysis of the ethical landscape of AI in HRM and offers policy recommendations to mitigate bias and enhance transparency.